Supertrde zaščitne prevleke - Panjan, Peter (Vakuumist, 1998)
Superhard coatings are those with hardness above 4000 Vickers. Very few candidates do exist, i.e. those wich form pure or nearly pure covalent bonds. Only certain compounds that consist of boron, carbon, nitrogen, and silicon can form such strong bonds. High hardness of an ideal system (monocrystal without defects) is related to a high value of the bulk modulus. Thus, a high valence charge density (high bond energy) along the tetrahedral bond (sp3), short bond distance and low polarisation (ionicity) along such a bond are necessary for a high value of the bulk modulus and hardness. However, hardness of real materials is a complex property, wich contains both elastic and plastic deformation. Therefore. hardness strongly depends on the microstructure of materials. To improve the hardness of materials we must inhibit the usual mechanisms leading to the fracture of crystalline and amorphous materials. The years ago, only very few candidates for duperhard coatings existed., like diamond, cubic boron nitride and boron carbide coatings. Nowdays, the number of superhard coatings is fast increasing and hardness of some of them (coatings in the form of superlattices and nanocrystalline composite) are close to that of diamond.
Keywords: nitridi; diamant; prevleke; trdota